Design and Simulation of a Multi Degrees of Freedom Adjustable Exoskeleton for Lower Limb Rehabilitation - Wei Xiao; Bi Wenlong; Li Yanan; Xu Beihao; Zhao Yanjun (Jixie chuandong)
Aiming at the rehabilitation training of patients with lower extremity damage and stroke, a multi-degree-of-freedom adjustable lower extremity rehabilitation exoskeleton is designed. The screw mechanism is used to replace the traditional leg structure, and there is a rotation module at the waist, which can better realize the human-machine collaboration. The lower extremity exoskeleton dynamics model is established by the Lagrangian method, and the theoretical torque is calculated; the lower extremity rehabilitation exoskeleton model is constructed, and the finite element simulation and exoskeleton kinematics/dynamics simulation are carried out using Ansys and Adams software, respectively. The results verify the rationality of the structural design, and provide a basis for the subsequent lower limb exoskeleton manufacturing and motor selection.